The role of ultrasonography in portal hypertension - Al-Nakshabandi Nizar (The Saudi Journal of Gastroenterology, 2006)
Portal hypertension is a commonly encountered clinical condition with multiple causes and several squeal. Ultrasound is an accurate non-invasive means of assessing its aetiology, severity and complications. I will review the role of ultrasonography in portal hypertension. The ultrasonic features that help identify its aetiology will be discussed as will the criteria that allow an assessment of disease severity and its complications.